Data on the effects of Glochidion zeylanicum leaf extracts in Caenorhabditis elegans - Duangjan, Chatrawee; Rangsinth, Panthakarn; Gu, Xiaojie; Zhang, Shaoxiong; Wink, Michael; Tencomnao, Tewin (Data in Brief, 2019)
The present article contains the data on the effects of Glochidion zeylanicum leaf extracts in C. elegans, which is related to the article " Glochidion zeylanicum leaf extracts exhibit lifespan extending and oxidative stress resistance properties in Caenorhabditis elegans via DAF-16/FoxO and SKN-1/Nrf-2 signaling pathways" Chatrawee et al., 2019. This dataset was generated to better understand the antioxidant and anti-aging properties of G. zeylanicum leaf extracts in C. elegans. The bioactive compounds of the extracts were analyzed using GLC-MS, LC-MS, and RP-HPLC. The antioxidant properties were determined using phenolics, flavonoids, ABTS and DPPH assays. The in vivo antioxidant properties were performed using the intracellular ROS accumulation and the survival rate under oxidative stress condition assays. The brood size, body length and life-span were determined regarding anti-aging properties in this data.